If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2k)+5=2(2k+1)+1
We move all terms to the left:
3(2k)+5-(2(2k+1)+1)=0
We calculate terms in parentheses: -(2(2k+1)+1), so:We get rid of parentheses
2(2k+1)+1
We multiply parentheses
4k+2+1
We add all the numbers together, and all the variables
4k+3
Back to the equation:
-(4k+3)
32k-4k-3+5=0
We add all the numbers together, and all the variables
28k+2=0
We move all terms containing k to the left, all other terms to the right
28k=-2
k=-2/28
k=-1/14
| q-8=2-q | | 6x+-6=24 | | 5e-9=51 | | h-10=-2 | | 92≤t≤98=97 | | 9(x-17)-12=-183 | | 10x+2=3x-61 | | 16x+10=9x+24 | | 14x+7=9x-8 | | 14x+7=6x-17 | | 10x+9=8x-1 | | 11x+9=6x-21 | | 13x+5=9x+17 | | 13x-5=7x-53 | | 6x-8=3x-32 | | 18x+2=9x-25 | | 15x-10=7x+54x= | | 14x-4=8x-64 | | 17x-7=10x-28 | | 12x-6=9x+21x= | | 12x-6=9x+21x | | 3w-7=w+19 | | 3(5x+8=33 | | –3(x+5)=(2x-10)/3 | | |x-3|+4=8 | | 7(5n+5)=4(7n-5)+8n | | 50=50-0.5x | | 4x+2∘+9x−3∘=90∘ | | ǀx+6ǀ=2x+8 | | 10x-5=-6 | | 4x+4=7x+22 | | 3x+8=2x+3–4x |